Tanfiż Taḥfīẓ Al-Qur´ān Bi Ma’had Al-Raḥmah Bi Bālikpāpān Fī Tanmiyah Istī’āb Al-Mufradāt Al-Lugah Al-‘Arabiyyah: تنفيذ تحفيظ القرآن بمعهد الرحمة بالكبابان في تنمية استيعاب المفردات اللغة العربية - Istianah, Istianah; Maslamah, Maslamah (ZAD Al-Mufassirin, 2023)
The implementation of memorizing the A-Qur'an using effective methods will support the quality of memorization owned by the students. The purpose of this study is to describe the implementation of the Qur'anic tahfiz in Ma'had Ar-Rahmah Balikpapan. This study used a descriptive approach and method. Based on the results of the study, the implementation of the Qur'an tahfiz in Ma'had Ar-Rahmah Balikpapan for students is divided into four levels based on one academic year. In daily memorization practice, students are divided into halaqahs under the supervision of a guide for each halaqah. Based on the order of time, students are asked to be able to memorize the Qur'an one page, and murajaah four pages of what they have memorized per day. With this, students are encouraged to be able to memorize one juz and murajaah four juz in one month.